210k views
2 votes
Given: y" - 2y' = 6t + 5e^2t. Find the correct form to use for y_p if the equation is solved using Undetermined coefficients. Do NOT Solve the equation

User Ziko
by
5.6k points

1 Answer

3 votes

Answer:


y_p=A+Bt+Ce^(2t)

Explanation:

Given:
y'' - 2y' = 6t + 5e^(2t).

we need to find the correct form for
y_p if the equation is solve using undetermined coefficients.

A first order differential equation
\frac{\mathrm{d} y}{\mathrm{d} x}=f\left ( x,y \right ) is said to be homogeneous if
f(tx,ty)=f(x,y) for all t.

Consider homogeneous equation
y''-2y'=0

Let
y=e^(rt) be the solution .

We get
(r^2-2r)e^(rt)=0

Since
e^(rt)\\eq 0,
r^2-2r=0.

So, we get solution as
y_c=c_1+c_2e^(2t)

As constant term and
e^(2t) are already in the R.H.S of equation


y, we can take
y_p as
y_p=A+Bt+Ce^(2t)

User Habib Rayan
by
5.1k points